The dynamics of nuclein acids content in Baltic cod tissues as the index of growth processes intensity - Ipatov, V.V. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1982)
Fish growth is one of the main indices which characterize the reaction of the species on environmental conditions, this determines the importance of this index when studying the dynamics of fish abundance. The aim of the given investigation was studying the dynamics of nuclein acids content in different tissues of Baltic cod for the estimation of the changes of protein growth intensity during the annual cycle in different years according to inhabitance conditions. It is shown that quantitative determinations of nuclein acids in cod tissues sensibly reflect changes in the intensity of growth processes. This permits to recommend to use this index when studying fish growth in different according to inhabitance conditions periods. Published Not Known